Duplication Cysts in the Oesophagus and Pylorus of a Juvenile Grey Seal (Halichoerus grypus): A Case Report - Kushnir, Andrew Y; Ng, Tiffany; Kilroy, David; Jahns, Hanne (Biology, Engineering, Medicine and Science Reports)
Duplication cysts of the gastrointestinal tract in mammals are rare congenital anomalies that arise during embryonic development. Finding these cysts in a juvenile Grey seal is also a rare observation. We report here a coincidental finding of two gastrointestinal duplication cysts in a 4-week-old female Grey seal, which was found on a beach on the East coast of Ireland. Gross anatomical features of the esophagus and pylorus together with the histological features of the cyst are presented.
Keywords: Seal; Stomach; Cyst; Gastrointestinal tract; Gross Anatomy